2014
DOI: 10.1007/s00436-014-3805-0
|View full text |Cite
|
Sign up to set email alerts
|

Do not forget the stool examination!—cutaneous and gastrointestinal manifestations of Blastocystis sp. infection

Abstract: Blastocystis sp. is one of the most common parasites in the human intestinal tract. This infection commonly is accompanied by diarrhoea and abdominal pain, but extraintestinal symptoms, such as skin lesions, may also accompany the disease. In this study, our aim was to assess the frequency, clinical symptoms and skin manifestations of confirmed positive Blastocystis sp. infections. Data of 80 patients with confirmed positive Blastocystis sp. infections were assessed retrospectively. The average age of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Symptoms persisted after initial antibiotic therapy but were finally eradicated after combined metronidazole and paromomycin treatment [22]. A recent retrospective study reported 8/80 (11%) Blastocystis infected patients to have skin manifestations as well as gastrointestinal symptoms [23]. Unfortunately this study relied solely on microscopy, so no information on ST related to cutaneous lesions can be gathered; however all of these studies do show the potential for Blastocystis to cause cutaneous symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms persisted after initial antibiotic therapy but were finally eradicated after combined metronidazole and paromomycin treatment [22]. A recent retrospective study reported 8/80 (11%) Blastocystis infected patients to have skin manifestations as well as gastrointestinal symptoms [23]. Unfortunately this study relied solely on microscopy, so no information on ST related to cutaneous lesions can be gathered; however all of these studies do show the potential for Blastocystis to cause cutaneous symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…There was a four‐fold increase in total serum IgE levels in urticaria patients with protozoa in comparison with those without protozoa. A recent retrospective study reported that 11.25% of enrolled patients, mainly women, exhibited skin manifestations associated with Blastocystis spp . However, by contrast with helminth infestations, the association between chronic urticaria and protozoa appears to be less clear.…”
Section: Urticaria As Symptom Of Parasite Infectionmentioning
confidence: 99%
“…Species of the genus Blastocystis are unusual, unicellular, enteric protozoan parasites present in humans throughout the world. In the healthy population, prevalences of this parasite have been reported at 30–50% in developing countries and 1.5–10.0% in developed countries . The prevalence of Blastocystis spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In a healthy population, the prevalence has been reported to be between 30%-50% and 1.5%-10.0%, in developing and developed countries, respectively. 2 People in the age range of years are mostly infected by Blastocystis. [3][4][5] In immunecompromised individuals, the prevalence of Blastocystis is about 30%-40% in developed countries.…”
mentioning
confidence: 99%